The Effect Of Compensation And Workload On Employee Loyalty At CV. Panca Aditiya Warman Bengkulu Tengah - Riska Wati; Sri Ekowati (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
The study aims to determine the effect of compensation and workload on employee loyalty at CV. Panca Aditiya Warman Bengkulu Tengah. Both partially and simultaneously. There are several factors that will be discussed in this study. Including compensation and workload. The objects in this study were all employes of CV. Panca Aditiya Warman Bengkulu Tengah totaling 45 people. In this study the author used data collection methods by means of observation and distribution of questionnaires. Data analysis techinques used in this study used instrument tests, classical assumption tests. Responden response analysis, multiple linear regression analysis, hypothesis testing and determination coefficient analysis (R2). The results of this study indicate that the compensation variable has a positive and significant effect on employee loyalty at CV. Panca Aditiya Warman Bengkulu Tengah. Thus, from the results of the research that has been conducted, it can be concluded that compensation and workload have a partial and simultaneous effect on employe loyalty at CV. Panca Aditiya Warman Bengkulu Tengah.